Valorization of Punica granatum L. Leaves Extracts as a Source of Bioactive Molecules - Sandra Marcelino; Filipa Mandim; Oludemi Taofiq; Tânia C. S. P. Pires; Tiane C. Finimundy; Miguel A. Prieto; Lillian Barros (MDPI AG, 2023)
Due to a lack of innovative valorization strategies, pomegranate processing generates a significant amount of residues with a negative environmental footprint. These by-products are a rich source of bioactive compounds with functional and medicinal benefits. This study reports the valorization of pomegranate leaves as a source of bioactive ingredients using maceration, ultrasound, and microwave-assisted extraction techniques. The phenolic composition of the leaf extracts was analyzed using an HPLC-DAD-ESI/MSn system. The extracts' antioxidant, antimicrobial, cytotoxic, anti-inflammatory, and skin-beneficial properties were determined using validated in vitro methodologies. The results showed that gallic acid, (-)-epicatechin, and granatin B were the most abundant compounds in the three hydroethanolic extracts (between 0.95 and 1.45, 0.7 and 2.4, and 0.133 and 3.0 mg/g, respectively). The leaf extracts revealed broad-spectrum antimicrobial effects against clinical and food pathogens. They also presented antioxidant potential and cytotoxic effects against all tested cancer cell lines. In addition, tyrosinase activity was also verified. The tested concentrations (50-400 µg/mL) ensured a cellular viability higher than 70% in both keratinocyte and fibroblast skin cell lines. The obtained results indicate that the pomegranate leaves could be used as a low-cost source of value-added functional ingredients for potential nutraceutical and cosmeceutical applications.